Reflection: Psychological Flow for Job-Seeking Adults with Autism - Daniel Kaufmann; Terri Ferguson-Lucas; Melissa A. Milliken (Journal of Scholarly Engagement)
Challenges faced by people with autism often present complications with finding success across multiple settings, which can include the workplace. As three counselor educators who have worked with individuals with Autism Spectrum Disorder (ASD), we have identified this as a common issue for ASD individuals seeking employment. This can involve numerous difficulties, including the maintaining of a form of work, which can be experienced successfully by the individual over time. Recently, it has been identified that utilization of Vocational Rehabilitation services has a significantly positive impact on employability of ASD youth at various levels of development. As with most supportive services, Vocational Rehabilitation (VR) approaches dramatically benefit from strength-based strategies for securing the forms of situational improvements ideally suited for the individual being served. People with autism present an additional challenge in the limited scope of activities, which are interesting enough to form a reasonable expectation that repetition will occur in a manner required by many entry-level jobs. It is beneficial for such individuals to participate in a supportive environment, with a set of task expectations that fall in range of their specific skillset. Achieving a balance between an individual’s skillset and the presented challenge leads to a phenomenon of the person becoming captivated by a given activity during a subconscious connection called “psychological flow.” This reflection explores the potential efficacy of using the principle of psychological flow development within the workplace and other related life areas typically encountered by those seeking to overcome interpersonal obstacles while improving task-related skillsets.